2010
DOI: 10.1111/j.1471-4159.2010.07055.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐spectrometry based oxidative lipidomics and lipid imaging: applications in traumatic brain injury

Abstract: Lipids, particularly phospholipids, are fundamental to central nervous system (CNS) tissue architecture and function. Endogenous polyunsaturated fatty acid chains of phospholipids possess cis-double bonds each separated by one methylene group. These phospholipids are very susceptible to free-radical attack and oxidative modifications. A combination of analytical methods including different versions of chromatography and mass spectrometry allows obtaining detailed information on the content and distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 116 publications
(137 reference statements)
2
81
0
Order By: Relevance
“…ROS formation occurs preferentially in mitochondria, and therefore it is accepted that CL is more susceptible to oxidation than other phospholipids. Moreover, because of the structural diversity of CL in brain, detecting hydroperoxide species of CL by MS is challenging, since CL oxidized species are likely to be overlap the natural brain CL species (Sparvero et al, 2010). In addition to the observed oxidation of CL, we also reported a decrease in the total content of CL after chronic unpredictable stress, which might be implicated in a decline of mitochondrial respiratory functions and ROS accumulation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…ROS formation occurs preferentially in mitochondria, and therefore it is accepted that CL is more susceptible to oxidation than other phospholipids. Moreover, because of the structural diversity of CL in brain, detecting hydroperoxide species of CL by MS is challenging, since CL oxidized species are likely to be overlap the natural brain CL species (Sparvero et al, 2010). In addition to the observed oxidation of CL, we also reported a decrease in the total content of CL after chronic unpredictable stress, which might be implicated in a decline of mitochondrial respiratory functions and ROS accumulation.…”
Section: Discussionmentioning
confidence: 67%
“…Lipid hydroperoxides are the primary products of lipid oxidation and have been used in several studies to evaluate the oxidation status of cells and/or tissues (Tyurin et al, 2008, Sparvero et al, 2010.…”
Section: Quantification Of Lipid Hydroperoxides In Mice Brain and Myomentioning
confidence: 99%
“…MALDI imaging appears to work particularly well for easily ionized lipids (PC, PE) as well as for other metabolites or peptides (88), and studies on the lipid content of a number of animal tissues have been reported, especially in the brain and liver, which have a high lipid content; this has been comprehensively reviewed recently (35,36). As yet, very few studies in which oxidized lipids were detected have been reported (114), but Stutts et al have used sophisticated MS n methodology to image truncated carboxylate-containing PCs in rat spinal cord and show they were mainly localized to the gray matter (Fig. 11) (124), and the analysis of oxidized lipids in traumatic brain injury has been recently reviewed (114).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Lipid metabolites are therefore considered potential biomarker candidates for disease diagnosis and drug responses. Indeed, recent lipidomic studies have shown that lipid metabolites such as eicosanoids and sphingolipids are biomarker candidates for cardiovascular events [1], traumatic brain injury [13], Alzheimer's disease [3,14], type 2 diabetes [15] and depression [16]. Blood is a commonly used biofluid for biomarker discovery because it is a ''data-rich'' source containing several thousands of hydrophilic and hydrophobic metabolites that likely reflect many complex biological processes in the body [17].…”
Section: Introductionmentioning
confidence: 99%